2005
DOI: 10.1128/iai.73.11.7705-7717.2005
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization Strategy To Impede Pilin-Mediated Binding ofPseudomonas aeruginosato Airway Epithelial Cells

Abstract: Prevention of pulmonary Pseudomonas aeruginosa infections represents a critical unmet medical need for cystic fibrosis (CF) patients. We have examined the tenet that a mucosal immunization approach can reduce interactions of a piliated form of this opportunistic pathogen with respiratory epithelial cells. Vaccinations were performed using ntPEpilinPAK, a protein chimera composed of a nontoxic form of P. aeruginosa exotoxin A (ntPE), where the C-terminal loop amino acid sequence of the PAK strain pilin protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…Nevertheless, antigenicity of this region can be improved by conjugation to carriers. Two chimeric proteins were constructed through insertion of different sizes of the DSL region of PAK strain in a non-toxic form of the ETA [138,139]. When administered subcutaneously into rabbits, it produced antibodies against both antigens, which reduced bacterial adherence and neutralised the cell-killing activity of ETA [138].…”
Section: Type 4 Pilimentioning
confidence: 99%
“…Nevertheless, antigenicity of this region can be improved by conjugation to carriers. Two chimeric proteins were constructed through insertion of different sizes of the DSL region of PAK strain in a non-toxic form of the ETA [138,139]. When administered subcutaneously into rabbits, it produced antibodies against both antigens, which reduced bacterial adherence and neutralised the cell-killing activity of ETA [138].…”
Section: Type 4 Pilimentioning
confidence: 99%
“…Furthermore, immunological studies indicated that the specific humoral immune response against DSL region can be protective in animal models (Cachia and Hodges ; Hsieh et al . ). The existence of this protective epitope, two β ‐turns conformational region and unique curved shape helps DSL zone to induce production of cross‐reactive antibodies against this region (Sheth et al .…”
Section: Introductionmentioning
confidence: 97%
“…It is of interest to determine all of the regions exposed to the environment under tension for understanding the extraordinary plasticity of GC-T4P filaments. In addition, by uncovering what regions of the pilus filament become exposed under strain, more effective drugs, acting as inhibitors to T4P binding, could potentially be engineered [13], [14].…”
Section: Introductionmentioning
confidence: 99%